Additive containing homo and heterolactic bacteria on the fermentation quality of maize silage - Daniel Junges (Acta Scientiarum. Animal Sciences, 2013)
This trial evaluated the addition of Lactobacillus plantarum , L. brevis and Enterococcus faecium combo additive against a control treatment. The silages were made in laboratory silos that were stored for 30, 60, 90 or 120 days before openin g. We evaluated the chemical composition of the forage before and after ensiling and the fermentative lo sses of silages. The additive decrea sed (p < 0.01) effluent production (11.4 kg ton -1 ) compared to control silage (14.0 kg ton -1 ), but it increased (p < 0.01) the Neutral Detergent Fiber (NDF) and Acid Detergent Fi ber (ADF) from 45.6% and 24.5% to 47.0 and 25.1% for control and additive silages, respectively. The storage periods affected (p < 0.01) effluent production, Dry Matter Losses (DML), NDF, ADF and pH vari ables. Fermentative losses were very low because of the adequate characteristics of maize for ensilage.